Child with autistic spectrum disorder: care from the family - Lina Domenica Mapelli; Mayara Caroline Barbieri; Gabriela Van Der Zwaan Broekman Castro; Maria Aparecida Bonelli; Monika Wernet; Giselle Dupas (Escola Anna Nery, 2018)
Abstract Objective: To know the experience of the family in the care of the child with Autism Spectrum Disorder (ASD) and to discuss possibilities of health care. Method: Descriptive research with qualitative approach, carried out with 15 families of children with ASD, living in two municipalities in the interior of the state of São Paulo, from October 2016 to March 2017. The Symbolic Interactionism was used as theoretical reference, and Narrative Analysis, as method. Results: Families perceive signs of autism, however, believe that there are not suspicious behaviors, but the child's personalities. When diagnosis is defined, family acceptance is painful and sad. The mother shows to be the main caretaker, while the father remains in the background. A significant change of direction of the family towards the care/attention/stimulation of the autistic child is observed. Conclusion: Unveiling family experience in the care of children with ASD amplifies strategies for reinforcement and adaptation.